من القمة إلى الأزمة: كيف تجاوز برشلونة أكبر تحد مالي في تاريخه - غول ،جيهاد (جامعة الوادي University of Eloued, 2025)
عانى نادي برشلونة لكرة القدم من أزمة مالية حادة بسبب الإنفاق المفرط على الصفقات ورواتب اللاعبين، إلى جانب تداعيات جائحة كوفيد-19 التي قلّصت الإيرادات وأدت إلى تفاقم الديون التي تجاوزت 1.35 مليار يورو. تفاقمت الأزمة مع عدم الامتثال لقوانين اللعب المالي النظيف، مما حدّ من قدرة النادي على تسجيل لاعبين جدد. لمواجهة ذلك، اتبعت الإدارة الجديدة استراتيجيات متعددة، شملت خفض التكاليف عبر تقليل الرواتب والتخلي عن بعض اللاعبين ذوي العقود المكلفة، وزيادة الإيرادات من خلال صفقات رعاية كبرى، وتفعيل الروافع المالية من خلال بيع جزء من حقوق البث التلفزيوني، كما لجأ النادي إلى إعادة هيكلة ديونه وتمديد فترات السداد لتخفيف الضغط المالي. بدأت هذه الخطوات تؤتي ثمارها، حيث سجل النادي أرباحًا في 2022/2023، لكن لا تزال هناك تحديات مثل الالتزام بسقف الرواتب، سداد الديون، واستعادة القدرة التنافسية. يعتمد مستقبل نادي برشلونة على تحقيق توازن مالي واستثمار مستدام لضمان استقراره على المدى الطويل. Barcelona Football Club has suffered a severe financial crisis due to excessive spending on deals and player's salaries, along with the fallout from the COVID-19 pandemic, which has reduced revenues and exacerbated debt exceeding 1.35 billion euros. The crisis worsened with non-compliance with fair financial play laws, limiting the club's ability to register new players. To address this, the new administration has pursued multiple strategies, including reducing costs by reducing salaries, abandoning some players with costly contracts, increasing revenues through major sponsorship deals, activating leverages by selling a portion of television rights, and restructuring its debts and extending repayment periods to relieve financial pressure. These steps are beginning to bear fruit, with the club registering profits in 2022/2023, but challenges remain such as adhering to the salary cap, repaying debts, and restoring competitiveness. FC Barcelona's future depends on achieving a financial balance and sustainable investment to ensure its long-term stability.
From top to crisis: How has Barcelona surpassed the biggest financial challenge ?in its history
مقال
Keywords: نادي برشلونة; أزمة مالية; قوانين اللعب المالي النظيف; الروافع المالية; fair financial; financial crisis; financial sustainability challenges